Escherichia Coli: From Genome Sequences to Consequence - Mark Pallen (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present article summarizes a presentation given by Professor Mark Pallen of the School of Medicine at the University of Birmingham (Birmingham, United Kingdom) for the Fourth Stanier Lecture held in Regina, Saskatchewan, on November 9, 2004. Professor Pallen's lecture, entitled 'Escherichia coli: From genome sequences to consequences', provides a summary of the important discoveries of his team of research scientists in the area of genetic sequencing and variations in phenotypic expression.